TYPES OF MEDIA AND TEACHING TECHNIQUES IN TEACHING SPEAKING AT SMP BRAWIJAYA SMART SCHOOL MALANG - Muh. Rajib Silmi (SUAR BETANG, 2017)
The aims of this research is to find out the teaching techniques and media used by the English teacher in teaching speaking to the seventh-grade students at SMP Brawijaya Smart School Malang. This is a case study research design. Instruments of this research are observation sheets, interview guides and documentation. The researcher observes all of the English teaching processes at the seventh-grade class. The researcher also interviews teachers and five students to get additional information. The documentation is used to confirm the data from observation. The result of the research shows that the English teachers use various teaching techniques namely question-answer display, translation, drilling, and discussion. The English teachers also use various teaching media namely human, printed, visual media and multimedia. However, the English teachers mostly use the question-answer display as teaching technique and printed media as the teaching media. Most students are interested in teaching techniques and the teaching media used by the teacher in teaching speaking. Based on the finding, the researcher has several suggestions for the English teacher and also for a further researcher. For the English teacher at SMP Brawijaya Smart School, the researcher suggests the teachers keep good things of teaching techniques and teaching media because the techniques are interesting. However, it will be better if the English teacher can give other teaching techniques and teaching media. Besides, it can also give the other views of the English teacher on teaching technique and teaching media. For further researchers, the study with a similar topic, the researcher suggests further researchers explore on more specific focus dealing with teaching technique or teaching media by conducting a research on more specific focus, it can be analyzed more deeply.